2014
DOI: 10.1016/j.gdata.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A ChIP-on-chip tiling array approach detects functional histone-free regions associated with boundaries at vertebrate HOX genes

Abstract: Hox genes impart segment identity to body structures along the anterior–posterior axis and are crucial for proper development. A unique feature of the Hox loci is the collinearity between the gene position within the cluster and its spatial expression pattern along the body axis. However, the mechanisms that regulate collinear patterns of Hox gene expression remain unclear, especially in higher vertebrates. We recently identified novel histone-free regions (HFRs) that can act as chromatin boundary elements dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Interspersed between the peaks of histone H3 enrichment, we observed a distinctive pattern of gaps, which we defined as histone free regions or HFRs (Srivastava et al, 2013). Using a bioinformatics approach to map the extent and location of the HFRs (Srivastava et al, 2014), we showed that the gaps in H3 binding mapped precisely to the intergenic regions separating adjacent Hox genes. This is recapitulated here for the Hoxd cluster ( Fig.…”
Section: Boundary Activity At the Vertebrate Hox Clusters: A Role Formentioning
confidence: 96%
“…Interspersed between the peaks of histone H3 enrichment, we observed a distinctive pattern of gaps, which we defined as histone free regions or HFRs (Srivastava et al, 2013). Using a bioinformatics approach to map the extent and location of the HFRs (Srivastava et al, 2014), we showed that the gaps in H3 binding mapped precisely to the intergenic regions separating adjacent Hox genes. This is recapitulated here for the Hoxd cluster ( Fig.…”
Section: Boundary Activity At the Vertebrate Hox Clusters: A Role Formentioning
confidence: 96%